Relationship Between the Use of Fitness Trackers and Smartwatches for Monitoring Physical Activity and the Sociodemographic Characteristics of Long-Term Care Residents During the COVID-19 Lockdown - Ivana Crnković; Karmen Lončarek; Nada Tomasović Mrčela; Danica Železnik; Tomislav Vlahović (Medicina)
Background and Objectives: The use of wearable fitness technology is a trend nowadays and has significant potential in promoting an active lifestyle among long-term care (LTC) residents. The objectives of this observational study were to examine the use of fitness trackers and smartwatches for monitoring physical activity and to analyze the relationship between the use of these technological solutions and the sociodemographic characteristics of LTC residents during the COVID-19 lockdown. Materials and Methods: Face-to-face interviews were conducted with 198 LTC residents stationed in eleven organizational units that provide long-term accommodation services for older adults in the city of Zagreb in Croatia. LTC residents aged 65 and older who receive the 1st level of accommodation services in the social care system according to their functional ability and health status were included in this study. Results: During the COVID-19 lockdown, 19.19% of LTC residents used wearable activity trackers. Gender (p = 0.0411) and education level (p = 0.0485) were recognized as significant sociodemographic predictors regarding the use of fitness trackers and smartwatches for monitoring physical activity. An odds ratio for gender of 0.454 (95% CI: 0.213–0.969) indicates that women have a 54.6% lower chance of using fitness trackers and smartwatches then men. The odds ratio for the education effects of 0.050 (95% CI: 0.003–0.980) demonstrates that there is a 95% lower chance of using fitness trackers and smartwatches for individuals with only elementary education as opposed to university graduates. Conclusions: The sociodemographic differences of LTC residents regarding the use of fitness trackers and smartwatches require further research, but they are also an incentive for the implementation of these technological solutions to protect the health of older adults.